Pengaruh Inovasi Jam Kerja Pelayanan Malam (Jajanan Malam) Terhadap Kualitas Pelayanan Publik di Kantor Kelurahan Satimpo Kota Bontang - Sela Saputri; Heryono Susilo Utomo (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2024)
The need for the community to obtain quality public services requires the government to make many efforts to improve services in order to meet the expectations of citizens. Such as government efforts, namely by creating innovative services. One of them in the Satimpo Village, Bontang City, created an innovation in the working hours of night services